KAJIAN TEORITIK PENGARUH GEOMETRI DAN BENTUK SUDU TERHADAP UNJUK KERJA TURBIN PROPELLER - PRASETYO, ARI (SENATIK STT Adisutjipto, 2017)
AbstractElectrical energy is one of the primary needs of Indonesian society that continues to increase. However, until now most of the electricity needs are still supplied by fossil fuel power plants. The fossil energy dependence affects the high cost of distributing electricity to remote areas. The picohydro power plant using propeller turbines is one solution for remote areas. The purpose of this paper is to conduct a theoretical study to obtain optimal propeller blade design with relatively easy design method. Based on the study results obtained geometry and design of turbine propeller that can produce efficiency 73,9% with head water 1,75 m and flowrate 64 l / s. While the propeller turbine design is the diameter of the turbine 200 mm the number of blades 5, and the inlet runner tip 65 °.